Increased cross-bridge recruitment contributes to transient increase in force generation beyond maximal capacity in human myocardium. (January 2018) - Milani-Nejad, Nima; Chung, Jae-Hoon; Canan, Benjamin D.; Fedorov, Vadim V.; Whitson, Bryan A.; Kilic, Ahmet; Mohler, Peter J.; Janssen, Paul M.L.
Abstract: Cross-bridge attachment allows force generation to occur, and rate of tension redevelopment ( k tr ) is a commonly used index of cross-bridge cycling rate. Tension overshoots have been observed briefly after a slack-restretch k tr maneuver in various species of animal models and humans. In this study, we set out to determine the properties of these overshoots and their possible underlying mechanism. Utilizing human cardiac trabeculae, we have found that tension overshoots are temperature-dependent and that they do not occur at resting states. In addition, we have found that myosin cross-bridge cycle is vital to these overshoots as inhibition of the cycle results in the blunting of the overshoots and the magnitude of the overshoots are dependent on the level of myofilament activation. Lastly, we show that the number of cross-bridges transiently increase during tension overshoots. These findings lead us to conclude that tension overshoots are likely due to a transient enhancement of the recruitment of myosin heads into the cross-bridge cycling, regulated by the myocardium, and with potential physiological significance in determining cardiac output. News and noteworthy: We show that isolated human myocardium is capable of transiently increasing its maximal force generation capability by increasing cross-bridge recruitment following slack-restretch maneuver. This process can potentially have important implications and significance in cardiac contraction in vivo. Highlights: Human myocardium can transiently increase its force generating capacity. This process involves a transient enhancement in cross-bridge recruitment. This physiological regulatory mechanism has potentially essential role in maintaining cardiac output.